Three-dimensional finite element analysis of varying diameter and connection type in implants with high crown-implant ratio - de Moraes, Sandra Lúcia Dantas; Verri, Fellippo Ramos [UNESP]; Santiago Júnior, Joel Ferreira; Almeida, Daniel Augusto de Faria; Lemos, Cleidiel Aparecido Araujo [UNESP]; Gomes, Jéssica Marcela de Luna [UNESP]; Pellizzer, Eduardo Piza [UNESP] (FapUNIFESP (SciELO), 2018)
The aim of this study was to evaluate the effect of varying the diameter, connection type and loading on stress distribution in the cortical bone for implants with a high crownimplant ratio. Six 3D models were simulated with the InVesalius, Rhinoceros 3D 4.0 and SolidWorks 2011 software programs. Models were composed of bone from the posterior mandibular region; they included an implant of 8.5 mm length, diameter Ø 3.75 mm or Ø 5.00 mm and connection types such as external hexagon (EH), internal hexagon (IH) and Morse taper (MT). Models were processed using the Femap 11.2 and NeiNastran 11.0 programs and by using an axial force of 200 N and oblique force of 100 N. Results were recorded in terms of the maximum principal stress. Oblique loading showed high stress in the cortical bone compared to that shown by axial loading. The results showed that implants with a wide diameter showed more favorable stress distribution in the cortical bone region than regular diameter, regardless of the connection type. Morse taper implants showed better stress distribution compared to other connection types, especially in the oblique loading. Thus, oblique loading showed higher stress concentration in cortical bone tissue when compared with axial loading. Wide diameter implant was favorable for improved stress distribution in the cortical bone region, while Morse taper implants showed lower stress concentration than other connections.
Keywords: Bone tissue; Dental implant; Finite element analysis; Mechanical stress